Persepsi Wisatawan Terhadap Kelestarian Lingkungan Di Kawasan Punclut Bandung - Irwan Irwan; Rusdin Tahir; Mohammad Liga Suryadana; Nurul Aldha Mauliddina Siregar; Fahriza Junizar; Aping Firman Juliansyah (EnviroScienteae, 2020)
Bandung is one of the best tourist destinations in Indonesia and Southeast Asia. Bandung has its own charm as a tourist spot with a variety of tourist attractions ranging from natural, culinary, heritage and cultural tourism. Tourism supports 40% of Bandung City's Regional Revenue and one of the tourist areas is Punclut. At first Punclut area was a green hills. Since the 1990s, there have been many travelers go to Punclut just to exercise in the morning. Now, there were more and more travelers with varied purposes, like for having meals or just hang out. Slowly, more and more commercial buildings were built in this area. Most of the designation is for restaurants. This conditions of course has an impact on the ecology of the area. Therefore, the authors conducted a study to determine an environmental sustainability in the Punclut area through the perceptions of tourists who have come to Punclut. The research was conducted using a qualitative method by conducting literature studies and distributing digital questionnaires through the Google Docs application. The results showed that environmental sustainability in the Punclut area was perceived by tourists who had visited there as "moderate" with a "good" tendency.